Understanding spiritual experience in Christian spirituality - S. P. Pretorius (Acta Theologica)
A spiritual experience for some means a mere fabrication of the mind. For others it is pathological and the consequence of psychiatric disturbances and psychological disorders. Others acknowledge that certain role-players are present when spiritual experiences occur. However, the identification of the involvement of these role-players by no means minimises the spiritual experience to a level of being non-significant. A spiritual experience in Christian spirituality assumes as its foundation that a personal relationship with Christ exists. It further signifies spiritual interaction as a result of the relationship. Taking different possibilities into account, this article contends that whatever scientists make of spiritual experience, it can never be reduced to mere fabrications of the mind, or psychological disorders. A spiritual experience in a Christian context signifies the interaction of God. Furthermore, spiritual experience is an important aspect of Christian spirituality that in essence indicates a relationship and interaction between the believer and God.